2013
DOI: 10.1097/qad.0b013e32835c208b
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics, safety and efficacy of tenofovir and emtricitabine in HIV-1-infected pregnant women

Abstract: Although pharmacokinetic exposure of the NRTIs TDF and FTC during pregnancy is approximately 25% lower, this was not associated with virological failure in this study and did not result in mother-to-child transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
79
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 39 publications
(46 reference statements)
14
79
1
1
Order By: Relevance
“…Of the three emtricitabine studies, the geometric mean ratio of cord to maternal plasma concentration was 1.2 in one study (n = 11); for this study the median time between dosing and delivery was 19 hours [13]. For the other emtricitabine study (n = 10), the median cord to maternal ratio was 1.6 but the median time between dosing and delivery was 8.5 hours [14]. For an emtricitabine case report (n = 1) the ratio was 1.7 at 13 hours after dosing [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three emtricitabine studies, the geometric mean ratio of cord to maternal plasma concentration was 1.2 in one study (n = 11); for this study the median time between dosing and delivery was 19 hours [13]. For the other emtricitabine study (n = 10), the median cord to maternal ratio was 1.6 but the median time between dosing and delivery was 8.5 hours [14]. For an emtricitabine case report (n = 1) the ratio was 1.7 at 13 hours after dosing [15].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies and a case report all included patients at steady-state, yet the median cord to maternal plasma concentration ratio varied from 0.82 (range 0.64-1.1, n=14) [14] in one study to 6.0 (range 3.5-7.2, n =3) [10] for the other; the case report (n = 1) was in between with a ratio of 1.1 [15]. Data for differences in time elapsed post-dose were not available for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated placental transfer, with drug concentrations approaching 1 g/ml in maternal and cord blood ratios for certain nucleoside (or nucleotide) reverse transcriptase inhibitors (NRTIs) (15)(16)(17)32) with slightly lower ratios reported for non-NRTIs (18)(19)(20) and even lower ratios for the protease inhibitors (16,21). Studies analyzing placental transfer of TFV have reported variable results, with maternal and cord blood concentration ratios ranging from 0.82 to 6.0 (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing placental transfer of TFV have reported variable results, with maternal and cord blood concentration ratios ranging from 0.82 to 6.0 (16,18). Protease inhibitors, such as atazanavir (22,23) and lopinavir (20,24) actively cross the placenta; however, undetectable concentrations in cord blood have been reported for nelfinavir, indinavir, and saquinavir (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…A similar European study also found no significant association overall between intrapartum intravenous AZT and MTCT, though it did not evaluate by viral load [17]. On the basis of a number of human studies [18][19][20], there does not seem to be any need for dose adjustment to maintain adequate drug levels for NRTIs in pregnancy. There is a trial in progress to assess women participating in a pre-exposure prophylaxis study who are taking TDF based therapies and become pregnant [21].…”
Section: Nucleos(t)ide Reverse Transcriptase Inhibitors (Nrti)mentioning
confidence: 98%